2022
DOI: 10.3389/feart.2022.929825
|View full text |Cite
|
Sign up to set email alerts
|

Buried depth calculation of the slope of the unstable rock based on natural vibration frequency

Abstract: The instability of the slope of the unstable rock poses a great threat to the safety of engineering and people’s lives and properties. The buried depth of an unstable rock is a key factor affecting its stability. It is difficult to directly measure the buried depth of the unstable rock. Therefore, it is of vital importance to indirectly and quickly identify the buried depth of the unstable rock. Assuming that the foundation soil is homogeneous and isotropic, the damping ratio is less than 1; it can be found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Deformation in the amplitude range is linear elastic, and the vibration model of the rock block can be simplified into a pendulum dynamic characteristic model, with the constitutive equation given by Eqs. 4, 5 (Jia et al, 2021):…”
Section: Modeling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Deformation in the amplitude range is linear elastic, and the vibration model of the rock block can be simplified into a pendulum dynamic characteristic model, with the constitutive equation given by Eqs. 4, 5 (Jia et al, 2021):…”
Section: Modeling Proceduresmentioning
confidence: 99%
“…The damage identification method of rock structures based on dynamic characteristic parameters can rapidly assess rock block stability. (Jia et al, 2021). However, the existing dynamic characteristic model is narrow in focus and does not accurately reflect the variation law of the dynamic characteristic parameters of rock masses in all failure modes.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, Song et al (2019a) investigated the effects of natural frequencies on the slope dynamic characteristics, and they concluded that the high-and low-frequency components mainly induce local and overall deformation of the surface slope of the rock, respectively. In order to achieve the stability evaluation of the perilous rock, Jia et al (2023aJia et al ( , 2022 found that the natural frequency increases nonlinearly in the horizontal direction with the increasing buried depth of the unstable rock, and they established the quantitative relationship model between the safety factor and natural frequency. Xie et al (2021) established a three-dimensional (3-D) analysis method for the rock vibration, and they proved the effectiveness for the rock stability analysis based on the natural frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al found that a ground-penetrating radar (GPR) survey can be used to evaluate the slope stability [29]. Du et al and Jia et al further conducted experimental research on dumping perilous rock and found that the natural vibration frequency is closely related to the stability [30][31][32][33]. However, the above research has just started and is in the experimental stage, and the theory has not yet been perfected [34,35].…”
Section: Introductionmentioning
confidence: 99%